SAT0426 High levels of employment but persisting work place impairment in patients with axial spondyloarthritis on biologic therapy. (15th June 2017) - Nadin, TG; Wallis, D; Holroyd, C; Clayton, P; Armstrong, R; Cooper, C; Davidson, B; Harvey, N; Dennison, E; Seth, R; Walker-Bone, KE; Bennett, S; et al.
Abstract : Background: Axial spondyloarthritis (axSpA) is associated with reduced work productivity. Biologic therapies have demonstrated a positive impact on work-related outcomes in clinical trials but real world data are limited. Objectives: To investigate the prevalence and predictors of work impairment and disability in patients with axSpA attending a biologic therapy clinic. Methods: Data were collected from a single-centre, prospective cohort of patients with axSpA treated with biologic therapy. Standardised outcome measures, including the Work Productivity and Activity Impairment (WPAI) Questionnaire for axSpA, are collected every 6 months. Data from the most recent clinic visit were analysed using IBM SPSS Statistics 24. Disease activity was compared between employed patients and those unemployed due to disability from axSpA. The effect of smoking status and gender on work related outcomes was analysed. The relationship between work-related outcomes and disease severity was investigated using Pearson's correlation. Significance was defined as p<0.05 with Bonferroni correction. Results: Data were available for 165 patients (mean age 47.6 years, 75% male, 21% current smokers). Mean time since diagnosis was 15.4 years and mean duration of biologic therapy 4.7 years, with 19/165 (12%) on a reduced dose regimen. Mean BASDAI was 4.0, ASQoL 6.6, BAS-G 3.9 and spinal pain VAS 4.0. Employment data were provided by 144 patients of whom 99/144 (69%) were employed; 17/144 (12%) not working due to disability caused by SpA; 19/144 (13%) retired; 5/144 (4%) unemployed; 2/144 (1%) full-time education; and 2/144 (1%) full-time parents. Of the 144 patients in employment, 8 (6%) had missed hours of work in the week prior to the last clinic visit due to axial SpA (mean hours missed =13). There was no difference between males and females in (i) the proportion of patients employed or (ii) the proportion not working due to disability from SpA. Mean impairment while working due to axial SpA was 23% and impairment of regular daily activities 35%. There was no significant difference in percentage work impairment between males and females. BASDAI was higher in patients unemployed due to SpA (7.1±1.6) compared to those who were employed (3.5±2.2, p<0.001). Higher levels of work impairment were observed in current smokers compared to previous smokers and never smokers (p=0.003). Positive correlations were found between individual WPAI domains and each of BASDAI, BAS-G, ASQoL and spinal pain VAS (p<0.001). Conclusions: In this cohort of axial SpA patients on biologic therapy, the majority were employed and few reported missing time at work. As expected, disease activity was higher in patients unemployed due to disability compared to those who were currently in paid work. Gender did not appear to affect employment rates, disability rates or work impairment. Smoking was associated with increased work impairment. The impact of disease on employment should be considered in the clinic and strategies for enhancing work participation directed towards those patients most at risk. Disclosure of Interest: T. Nadin: None declared, D. Wallis Grant/research support from: Janssen, MSD and Pfizer, C. Holroyd Paid instructor for: BMS, Abbvie, Chugai and Janssen., P. Clayton: None declared, R. Armstrong: None declared, C. Cooper: None declared, B. Davidson: None declared, N. Harvey: None declared, E. Dennison: None declared, R. Seth: None declared, K. Walker-Bone: None declared, S. Bennett: None declared, C. Edwards Consultant for: Abbvie, Pfizer, Lilly, Celltrion, Mundipharma, Samsung, Anthera, UCB, Celgene, Roche, BMS, Jansen, Novartis and UCB., Speakers bureau: Abbvie, Pfizer, Lilly, Celltrion, Mundipharma, Samsung, Anthera, UCB, Celgene, Roche, BMS, Jansen, Novartis and UCB.